Mechanism and Experiment of Full-Feeding Tangential-Flow Picking for Peanut Harvesting - Lili Shi; Bing Wang; Zhichao Hu; Hongguang Yang (Agriculture, 2022)
Peanut is China’s most competitive oil and cash crops internationally. Furthermore, China’s peanut production is the largest in the world. Hence, the peanut industry plays an important role in the national economy. To address the problems of high rates of broken and unharvested pods during peanut harvesting, we researched the dynamic characteristics of harvesting and the mechanisms that influence operation quality. Considering the typical peanut varieties in China’s main peanut-producing areas as the study objects, we studied the mechanical properties of peanut in relation to the harvesting process. By adopting the Box-Behnken design, we set the harvesting net rate Y1, breakage rate Y2, and entrapment loss rate Y3 as the evaluation indices. We performed response surface testing on the peanut-harvesting roller speed, longitudinal size of concave sieve holes, peanut harvesting gap, and feeding volume. Through field verification testing, the parameters for maximum performance were obtained. When the picking roller speed was 260 r/min, the longitudinal dimension of the concave grate sieve pores was 90 mm, the harvesting gap was 40 mm, and the feed rate was 3.3 kg/s. Moreover, the harvesting net rate, breakage rate, and entrapment loss rate were 94.61%, 3.78%, and 0.85%, respectively. Verification testing was carried out based on the optimal parameters, and the results showed that the harvesting net rate, breakage rate, and entrapment loss rate were 95.73%, 3.54%, and 0.84%, respectively. A comprehensive scheme to optimize the peanut harvesting process was proposed to overcome harvesting problems and improve harvest quality. The study conclusions provide theoretical guidance for developing improved tangential-flow peanut-harvesting technology and equipment.